Menetrey-Willam numerical model for analysis of fiber reinforced concrete beams - Lucas Meira Santos; Paulo Roberto Lopes Lima; Geraldo José Belmonte dos Santos (Revista IBRACON de Estruturas e Materiais)
Abstract The introduction of fibers into cement-based materials alters, among other things, the stress-strain diagram in both tension and compression, necessitating changes in behavior models and structural design. This study evaluated the effect of stress-strain curves on the behavior of Fiber Reinforced Concrete (FRC) beams, using ANSYS software for modeling based on the finite element method (FEM). The Menetrey-Willam model, supported by the Willam-Warkne yield surface, was chosen to represent the mechanical behavior of fiber-reinforced concrete. The adopted model is capable of simulating elasticity, plasticity, tension stiffening, large displacements and deformations. To verify and validate the model, numerical simulations were conducted on FRC's behavior under compression and indirect tension (bending), and on beams subjected to 4-point tests, comparing numerical results with experimental data. The simulations demonstrated agreement with laboratory tests in tension, compression, and beam bending, affirming the feasibility of incorporating fiber effects into computer modeling, thereby modifying concrete properties. Specifically, beams subjected to flexural failure exhibited numerical responses similar to the experimental results, demonstrating the model's ability to represent the influence of fiber reinforcement on structural failure modes.